The interaction of psychological and physiological homeostatic drives and role of general control principles in the regulation of physiological systems, exercise and the fatigue process - The Integrative Governor theory - St Clair Gibson, A.; Swart, J.; Tucker, R. (European Journal of Sport Science, 2018)
Either central (brain) or peripheral (body physiological system) control mechanisms, or a combination of these, have been championed in the last few decades in the field of Exercise Sciences as how physiological activity and fatigue processes are regulated. In this review, we suggest that the concept of `central` or `peripheral` mechanisms are both artificial constructs that have `straight-jacketed` research in the field, and rather that competition between psychological and physiological homeostatic drives is central to the regulation of both, and that governing principles, rather than distinct physical processes, underpin all physical system and exercise regulation. As part of the Integrative Governor theory we develop in this review, we suggest that both psychological and physiological drives and requirements are underpinned by homeostatic principles, and that regulation of the relative activity of each is by dynamic negative feedback activity, as the fundamental general operational controller. Because of this competitive, dynamic interplay, we propose that the activity in all systems will oscillate, that these oscillations create information, and comparison of this oscillatory information with either prior information, current activity, or activity templates create efferent responses that change the activity in the different systems in a similarly dynamic manner. Changes in a particular system are always the result of perturbations occurring outside the system itself, the behavioural causative `history` of this external activity will be evident in the pattern of the oscillations, and awareness of change occurs as a result of unexpected rather than planned change in physiological activity or psychological state.